2017
DOI: 10.1155/2017/4792489
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effect of Light-Emitting Diode Irradiation on Incised Wounds Is Correlated with Changes in Cyclooxygenase 2 Activity, Prostaglandin E2, and Proinflammatory Cytokines

Abstract: Background. Light-emitting diode (LED) phototherapy has been reported to relieve pain and enhance tissue repair through several mechanisms. However, the analgesic effect of LED on incised wounds has never been examined. Objectives. We examined the analgesic effect of LED therapy on incision pain and the changes in cyclooxygenase 2 (COX-2), prostaglandin E2 (PGE2), and the proinflammatory cytokines interleukin 6 (IL-6), IL-1β, and tumor necrosis factor α (TNF-α). Methods. Rats received LED therapy on incised sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Colon tissue samples were lysed in a RIPA buffer containing a 2% phosphatase inhibitor (Thermo Scientific) and a 1% mammalian‐protease inhibitor (Sigma‐Aldrich). The membranes were incubated with the following primary antibodies overnight 28 : Invitrogen (1:100): Zonula Occludens‐1 (ZO‐1) and Occludin (1:100, Invitrogen); Claudin‐1 and Junctional adhesion molecule‐A (JAMA, 1:500, Invitrogen); ChAT, NGF, GDNF, sub‐P, tryptase, and GAPDH (1:100, 1:10 000‐internal loading control, Abcam); and PGE2 polyclonal antibody (1:200) (Bioss Inc) 29 . They were incubated with ECL AP‐conjugated anti‐rabbit/mouse IgG (1:3000; GE Healthcare) for 90 minutes in room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Colon tissue samples were lysed in a RIPA buffer containing a 2% phosphatase inhibitor (Thermo Scientific) and a 1% mammalian‐protease inhibitor (Sigma‐Aldrich). The membranes were incubated with the following primary antibodies overnight 28 : Invitrogen (1:100): Zonula Occludens‐1 (ZO‐1) and Occludin (1:100, Invitrogen); Claudin‐1 and Junctional adhesion molecule‐A (JAMA, 1:500, Invitrogen); ChAT, NGF, GDNF, sub‐P, tryptase, and GAPDH (1:100, 1:10 000‐internal loading control, Abcam); and PGE2 polyclonal antibody (1:200) (Bioss Inc) 29 . They were incubated with ECL AP‐conjugated anti‐rabbit/mouse IgG (1:3000; GE Healthcare) for 90 minutes in room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…#3025S, Cell signaling); PGES2 (Cat. #bs-2639R, Bioss) [86, 87]; and GADPH (Cat.# SC-32233, Santa Cruz Biotechnology). Secondary antibodies used were as follows: goat antirabbit-800 (LI-COR, P/N 925–32211) and donkey antimouse-680 (LI-COR, P/N 925–68075).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to opioid receptors, current research has also found that low-level laser therapy's inhibitory effect on pain may be related to cytochrome c oxidase (44), cyclooxygenase (35), and various proinflammatory cytokines (45). The underlying molecular mechanism behind the analgesic effect of CO 2 laser irradiation remains unclear.…”
Section: Discussionmentioning
confidence: 99%